Analisi Sebaran SMA Negeri di Kabupaten Pringsewu Tahun 2017 - Ihwan Faozi; Edy Haryono; Dedy Miswar (JPG (Jurnal Penelitian Geografi), 2018)
This research investigated about: (1) The distribution pattern of state senior high school (SMA Negeri) in Pringsewu District. (2) The accessibility of state senior high schools in Pringsewu District. (3) comparison of population senior high school with the number of classrooms for each state senior high school in Pringsewu District. The subjects of this research were 10 state senior high schools in Pringsewu District. The objects of this research distribution, accessibility and comparison of population senior high school with the number of classrooms for each state senior high school in Pringsewu District. Data collecting technique in this research were observation and documentation. The result showed: (1) The distribution pattern of state senior high schools in Pringsewu District was random. (2) Accesibility senior high schools in Pringsewu District is easly categorized. (3) Comparison of classrooms in Pringsewu District is more 14 class room.Penelitian ini bertujuan untuk mengkaji: (1) sebaran SMA Negeri di Kabupaten Pringsewu. (2) Aksesibilitas SMA Negeri di Kabupaten Pringsewu. (3) Perbandingan antara jumlah penduduk usia sekolah menengah dengan jumlah ruang kelas sekolah menengah di Kabupaten Pringsewu. Metode penelitian yang digunakan adalah metode penelitian survei. Subjek penelitian ini adalah 10 SMAN di Kabupaten Pringsewu. Objek penelitian ini yaitu sebaran, aksesibilitas dan perbandingan antar jumlah penduduk usia SMA dengan jumlah ruang kelas SMA di Kabupaten Pringsewu. Pengumpulan data dilakukan dengan teknik observasi dan dokumentasi. Hasil penelitian menunjukkan: (1) pola sebaran SMA Negeri di Kabupaten Pringsewu adalah random (acak). (2) Aksesibilitas SMA Negeri di Kabupaten Pringsewu dikategorikan mudah. (3) Perbandingan ruang kelas di Kabupaten Pringsewu lebih 14 ruang kelas.Kata Kunci: aksesibilitas, pemetaan, sekolah